An event of extreme relativistic and ultra-relativistic electron enhancements following the arrival of consecutive corotating interaction regions: Coordinated observations by Van Allen Probes, Arase, THEMIS and Galileo satellites - Nasi, Afroditi; Katsavrias, Christos; Daglis, Ioannis A.; Sandberg, Ingmar; Aminalragia-Giamini, Sigiava; Li, Wen; Miyoshi, Yoshizumi; Evans, Hugh; Mitani, Takefumi; Matsuoka, Ayako; Shinohara, Iku; Takashima, Takeshi; et al. (Frontiers in Astronomy and Space Sciences, 2022)
During July to October of 2019, a sequence of isolated Corotating Interaction Regions (CIRs) impacted the magnetosphere, for four consecutive solar rotations, without any interposed Interplanetary Coronal Mass Ejections. Even though the series of CIRs resulted in relatively weak geomagnetic storms, the net effect of the outer radiation belt during each disturbance was different, depending on the electron energy. During the August-September CIR group, significant multi-MeV electron enhancements occurred, up to ultra-relativistic energies of 9.9 MeV in the heart of the outer Van Allen radiation belt. These characteristics deemed this time period a fine case for studying the different electron acceleration mechanisms. In order to do this, we exploited coordinated data from the Van Allen Probes, the Time History of Events and Macroscale Interactions during Substorms Mission (THEMIS), Arase and Galileo satellites, covering seed, relativistic and ultra-relativistic electron populations, investigating their Phase Space Density (PSD) profile dependence on the values of the second adiabatic invariant K, ranging from near-equatorial to off equatorial mirroring populations. Our results indicate that different acceleration mechanisms took place for different electron energies. The PSD profiles were dependent not only on the μ value, but also on the K value, with higher K values corresponding to more pronounced local acceleration by chorus waves. The 9.9 MeV electrons were enhanced prior to the 7.7 MeV, indicating that different mechanisms took effect on different populations. Finally, all ultra-relativistic enhancements took place below geosynchronous orbit, emphasizing the need for more Medium Earth Orbit (MEO) missions.